2020
DOI: 10.1016/j.celrep.2020.108182
|View full text |Cite
|
Sign up to set email alerts
|

Local Efficacy of Glutamate Uptake Decreases with Synapse Size

Abstract: Highlights d Relative astrocytic coverage of glutamatergic spines decreases with spine size d Control of perisynaptic glutamate transients by uptake decreases with spine size d Control of receptor-mediated Ca 2+ entry by uptake decreases with spine size d Accordingly, small spines are better shielded from invading glutamate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 64 publications
1
81
0
1
Order By: Relevance
“…Thus, in situ glutamate dynamics are extremely complex and depend on many factors in addition to overall transporter expression levels. For example, glutamate clearance rates depend on the proximity of perisynaptic astrocytic processes to the synapse (Henneberger et al, 2020), synapse size (Herde et al, 2020), astrocyte resting membrane potential (Djukic et al, 2007), transporter surface mobility (Murphy-Royal et al, 2015) as well as the architecture and tortuosity of the extracellular space (Hrabětová, 2005). Posttranslational modifications of glutamate transporters, including phosphorylation and palmitoylation, can also influence transporter-mediated uptake (Casado et al, 1993;Huang et al, 2010;Pita-Almenar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in situ glutamate dynamics are extremely complex and depend on many factors in addition to overall transporter expression levels. For example, glutamate clearance rates depend on the proximity of perisynaptic astrocytic processes to the synapse (Henneberger et al, 2020), synapse size (Herde et al, 2020), astrocyte resting membrane potential (Djukic et al, 2007), transporter surface mobility (Murphy-Royal et al, 2015) as well as the architecture and tortuosity of the extracellular space (Hrabětová, 2005). Posttranslational modifications of glutamate transporters, including phosphorylation and palmitoylation, can also influence transporter-mediated uptake (Casado et al, 1993;Huang et al, 2010;Pita-Almenar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, it can be concluded that if the local transporter density is slightly up- or down-regulated, this will result in a shorter or larger SARGe. This connection puts astrocytes in an ideal position to tune synaptic cross-talk by strategic positioning of glutamate transporter molecules or their membranes, eg ( 67, 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, invasion of the synaptic cleft by astrocytic processes in Connexin 30 knockout mice increased the control of synaptic transmission by glutamate uptake (Pannasch et al, 2014). Along these lines, we recently demonstrated that spine size negatively correlates with the local efficacy of glutamate uptake in the hippocampus (Herde et al, 2020). Another study suggested that rearrangements of the astrocytic cytoskeleton induced changes in glutamate uptake which were linked to altered activity of the Na + /K + -ATPase (Sheean et al, 2013).…”
Section: Localization Of Glutamate Transportersmentioning
confidence: 91%
“…However, after escaping the synaptic cleft, the radius of action of glutamate is determined by diffusion and the hindrance thereof either by physical barriers or by binding and uptake by transporters (Zheng et al, 2008;Scimemi and Beato, 2009). Hence, glutamate transporters located close to the synaptic cleft limit the diffusion of glutamate to extrasynaptic sites, where high-affinity N-methyl-D-aspartate receptors (NMDARs) and metabotropic glutamate receptors (mGluRs) are localized, and prevent the spillover to neighboring neurons (Scimemi et al, 2004;Zheng et al, 2008;Henneberger et al, 2020;Herde et al, 2020).…”
Section: Localization Of Glutamate Transportersmentioning
confidence: 99%
See 1 more Smart Citation